Pengembangan Video Pembelajaran Berbantuan Aplikasi Plotagon Pada Materi Memaparkan Informasi Dari Teks Narasi Sejarah - Ersila Devy Rinjani Ersila; Fahru Umar Syarif; Asma’ul Husna (Elementary Teacher Education Program, Majalengka University, 2023)
Learning media is an absolute necessity in a learning process. Unfortunately, the learning media available on the market or even schools have not been able to answer the needs of teachers in delivering learning material. Including the absence of learning videos specifically designed for historical narrative text material. The purpose of this study was to determine the analysis of the needs, characteristics, and student responses to the Plotagon application-assisted learning videos. This study uses the Research and Development method. Collecting data using the method of documentation, interviews, observation, questionnaires (questionnaire). The results of the study show that the Plotagon application-assisted learning videos are declared very feasible to be tested on students. The validation results from material experts obtained an average value of 86.8% and from media experts obtained an average value of 89.28%. The results of the teacher's response to the Plotagon application-assisted learning video media received an